Motivasi belajar peserta didik kelas IV sekolah dasar pada pembelajaran STEAM di masa pandemi covid-19 - Khikmawati Khikmawati; Hadi Mulyono; Fadhil Purnama Adi (Universitas Sebelas Maret, 2022)
Education system in Indonesia is experiencing new challenges due to the Covid-19 pandemic. Students learn form the home to avoid the spread of the corona virus. Changes ini learning methods form face to face in the calssroom to online learning have na impact on learning quality, motivation, and learning success. In this 21st century learning, studnets are required to continue o improve their academic mastery and implement it in everyday life. In hoped that STEAM (Science, Technology, Engineering, Art, and Mathematics) learning in this pandemic will be able to train 21st century skill for students. This reseacrh uses a descriptive quualitative approach, with purposive sampling technique. The subjects in this study were elementary school fourth grade students. In STEAM learning during the covid-19 pandmeic, the level of motivation of the subjects was different. The different in motivation due to the intrinsic and axtrinsic factors of the studnet. This research data analysis using the results of observations, interviews, and documentation.teh result of this study show that in general teh learning motivation of students in STEAM learning is quite good even in the condition of the covid-19 pandemic.